Efektivitas Berkumur Seduhan Teh Putih (Camellia Sinensis L.) Terhadap Indeks Plak Gigi - Hinggadita Adjeng Noorfadhila; Retno Kusniati; Nur Khamilatusy Sholehah (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2019)
Tea is the most popular beverage product that is consumed by many people in Indonesia and the world community because tea has a distinctive taste and aroma. Tea contains a rich source of polyphenols (catechins) which are part of flavonoids that can inhibit the growth of Streptococcus mutans, Streptococcus sobrinus and Lactobacillus which are bacteria that cause dental plaque formation. Purpose, to analyze the effectiveness of white tea (camellia sinensis L.) gargling on the dental plaque index. Method, quasi experiment with pre and posttest control group design. This research was conducted at the Faculty of Dentistry, University of Muhammadiyah Semarang with a total of 36 samples taken by random sampling technique. The treatment group (white tea) and the control group (0.2% chlorhexidine) were calculated using the PHP-M plaque index. The value of plaque index before gargling in white tea steeping had an average value of 1.77 ± 0.60 and the value of the plaque index after gargling in steeping white tea had an average value of 1.18 ± 0.48. The results of the statistical analysis dependent test t test showed p = 0,000 (p<0.005) so that there were significant differences between the plaque indices in the white tea group before and after treatment. The results of the independent statistical t test showed that the chlorhexidiene control group was 0.2% p = 0.024 (p<0.005) and white tea p = 0.003 (p<0.005). It was concluded that white tea was more effective than chlorhexidine 0.2%. Conclusion, Gargling of white tea steeping is effective in decreasing dental plaque index.